Effect of frequent weighing on the performance of growing rabbits - Rashwan, A. A.; Szendrő, Zsolt; Biróné Németh, Edit; Radnai, István (Acta Agraria Kaposváriensis, 2007)
The aim of the experiment was to study the effects of frequent weighing on the performance of Pannon White growing rabbits. Rabbits were weaned at 21 (n = 108) or at 35 days of age (n = 108). Both groups were halved. One part of the rabbits was weighed weekly (frequently) and the others were weighed only at the beginning and at the end (70th day of age) of the experiment (control). There were no significant differences between the frequently weighed and control groups in body weight, feed intake and feed conversion. The mortality was independent of the treatments and it was higher in the control group in case of 21d weaning and among frequently weighed rabbits weaned at 35 days. Experimental results show that the frequently weighed rabbits reach identical performance with control group.
Keywords: rabbits; weighing; body weight; feed intake; mortality